Saving more lives on time: Strategic policy implementation and financial inclusion for safe abortion in Indonesia during COVID-19 and beyond - Saraswati, Putri Widi (Frontiers in Global Women's Health, 2022)
Abortion is common in Indonesia, with 79% being unsafe. Unsafe abortion is one of the top five causes of maternal deaths globally. Meanwhile, in Indonesia, the maternal mortality rate (MMR) is still high, with up to 30% of it being related to unsafe abortion. In the COVID-19 pandemic, the number of unsafe abortions is expected to increase along with a 15–30% increase in unintended pregnancies. This will add to the number of maternal deaths on top of direct deaths caused by COVID-19. In Indonesia, access to safe abortion is still limited based on grounds. There are also gaps in implementation and in the financing mechanism of legal safe abortion, especially in the era of the national health insurance scheme (Jaminan Kesehatan Nasional/JKN). This brief aims to guide how to equitably implement and inclusively finance safe abortion in Indonesia—in and beyond the COVID-19 pandemic—to gain maximum socioeconomic benefit and leave no one behind.